Swift heavy ion effects in gallium nitride - Mansouri, S.; Marie, P.; Dufour, C.; Nouet, G.; Monnet, I.; Lebius, H.; Benamara, Z.; Al-Douri, Y. (Universiti Malaysia Perlis, 2008)
Link to publisher's homepage at http://www.unimap.edu.my/ ; Open access only applicable for vol. 1; issue 1, 2008.